Affordances do celular e potencialidades do celular e potencialidades do Whatsapp no trabalho com as habilidades orais em português língua adicional (LPA) - Camila de Souza Santos (2019)
From 2013 onwards in Brazil, access to the internet via mobile devices has expanded the possibilities of communication and socialization between users, and the field of language learning is inserted in the same context of social influence. Mobile learning in language teaching has now become consolidated, yet it lacks further reflections on the relationship between learners and their electronic devices in the context of oral competence activities. Given this, this paper aims to 1) identify the affordances indicating the perception of learners regarding the use of mobile phones and the WhatsApp application as support for oral production in Portuguese as a Foreign Language (PFL); 2) identify mobile applications that can contribute to oral development in PFL; 3) discuss aspects regarding the incorporation of the WhatsApp application as an opportunity-enhancing resource during the preparation for the Celpe-Bras Exam interview. The experience analyzed in this study was attended by six international students, aged between 18 and 23, candidates for the Exchange Program for Undergraduate Students (PEC-G) at a Brazilian public university. This study is based on the theoretical assumptions of mobile and ubiquitous learning (CROMPTON, 2013; PEGRUM, 2014; YAHYA et al., 2010; SACCOL, SCHLEMER, 2011; GREFF et al., 2018), the ecological approach (VAN LIER, 2002; 2010), and the Affordance Theory (GIBSON, 1986; NORMAN, 1999, 2013; STROFEGEN, 2003; PAIVA, 2010). A 12-week training via WhatsApp supported the collection of data from interviews and questionnaires. This experience allowed us to verify that the most prominent affordance involving the use of WhatsApp concerns the indirect work of oral production, that is, listening to the researcher’s feedbacks directed to the different research participants. Other affordances such as producing a speech script, recording different audio versions, listening to the audio itself, and listening to the audio produced by the classmates appear to be quite balanced in the study, being mentioned in the appropriations of half of the apprentices investigated (three out of six). Regarding affordances focused on oral production and comprehension related to other mobile applications, YouTube has stood out compared to other streaming platforms. Finally, the use of dictionaries as support for the practice of pronunciation comprehension, and oral production and comprehension through language learning applications were also balanced affordances, being mentioned by half of the participant learners (three out of six). These results indicate that the use of mobile devices and applications can be combined with the oral skills development process, acting as a complement to in-class foreign language.